Complete Reduction of Leg Lymphedema after Liposuction: A 5-Year Prospective Study in 67 Patients without Recurrence - Tobias Karlsson, MD, PhD; Mattias Hoffner, MD, PhD; Karin Ohlin, OTR; Barbro Svensson, RPT, LT; Håkan Brorson, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Lymphedema leads to adipose tissue deposition that cannot be removed using conservative methods. Previous studies have shown a complete reduction in excess volume in limbs with lymphedema when treated with liposuction and controlled compression therapy (CCT). We present the long-term outcomes of all patients treated with liposuction and CCT for lower extremity lymphedema (LEL) who were followed up for 5 years. Methods:. Sixty-seven LEL patients underwent liposuction and CCT. Thirty-six patients had primary lymphedema and 31 patients had secondary lymphedema. The outcomes included excess leg volume over a follow-up period of 5 years. Any association between patient characteristics and treatment outcomes was analyzed. Results:. The preoperative excess volume prior was 3515 mL [interquartile range (IQR): 2225–5455 mL], and the volume ratio to the unaffected leg was 1.35 (IQR: 1.25–1.53). One year after treatment, the excess volume decreased by 101% (IQR: 84–116). The decrease in excess volume continued during the 5-year follow-up, and at the end of the study, the excess volume had decreased by 115% (IQR: 98–124). No major complications were noted. Conclusions:. Liposuction and CCT are safe and effective procedures for removing excess adipose tissue and normalizing the leg volume in patients with late-stage LEL. When no satisfactory results are obtained with conservative methods, such as complex decongestive therapy, and there is no or minimal pitting on limb examination, excess adipose tissue is present, and liposuction can be considered.